The potential of RFID technology in Blood Center processes - Kebo, V; Klement, P; Cermáková, Z; Gottfried, J; Sommerová, M; Palecek, A (Studies in health technology and informatics, 2010)
Current RFID technology deployment is limited by safety, procedural and physical limitations in healthcare field. It is important to define and ensure safe operation of technologies without actual deployment in real operation. Potential problems could arise due to the consequences of technical and physical characteristics of RFID technology and its improper location. This article deals with manipulation of blood products and the definition of suitable places for radio identification. Each suitable place must undergo laboratory experiments and tests. The results can provide a convenient base for defining efficient and safe deployment of RFID technology in Blood Centers with substantial financial savings for Czech healthcare.
Keywords: Blood Banks; označování výrobků; krevní banky; identifikace na rádiové frekvenci - prostředky; Product Labeling; Radio Frequency Identification Device